Messenger ribonucleic acid levels in disrupted human anterior cruciate ligaments - Lo, Ian K Y; Marchuk, Linda; Hart, David A; Frank, Cyril B (Clinical orthopaedics and related research, 2003)
Thirty patients had anterior cruciate ligament reconstruction for ongoing instability. Two groups were defined according to gross morphologic features identified during reconstruction: anterior cruciate ligament disruptions with scars attached to a structure in the joint and disruptions without reattachments. Reverse transcription polymerase chain reaction for a subset of extracellular matrix molecules, proteinases, and proteinase inhibitors was done on samples of scarred anterior cruciate ligament tissue removed during reconstructive surgery. Results of the nonattached scar group showed significantly increased mRNA levels for Type I collagen, and an increased Type I to Type III collagen ratio compared with that for the attached scar group. In the first year after injury, decorin mRNA levels in the nonattached scar group also were significantly higher than in the attached scar group. Biglycan mRNA levels in the nonattached scar group correlated closely with Type I collagen mRNA levels. These results suggest differences in cellular expression in torn anterior cruciate ligaments that attach to structures in the joint versus those which do not. Although the molecular mechanisms responsible for these differences have not been delineated, different molecular signals may influence the gross morphologic features of anterior cruciate ligament disruptions or alternatively, differing gross morphologic features may be subject to different mechanical loads leading to altered molecular expression. However, the finding of endogenous cellular activity in injured anterior cruciate ligaments raises the possibility that this activity may be enhanced to improve outcomes.